Growth of Ornamental Grasses Under Salinity Stress - Henschke Monika (Journal of Horticultural Research, 2016)
The aim of this study was to determine the effect of substrate salinity caused by increasing NaCl doses on growth and development of ornamental grasses: Briza media L., Deschampsia cespitosa (L.) P. Beauv., Koeleria glauca (Spreng.) DC., Sesleria caerulea (L.) Ard. and Sorghastrum nutans (L.) Nash. Results provide the basis for the preliminary classification of analyzed grasses in terms of their tolerance to substrate salinity. Grasses, responding negatively to substrate salinity caused by small doses of 5 and 10 g·NaCl·dm−3, may be considered to be sensitive species. Within the studied genotypes, B. media showed a negative response to salt stress in most of the analyzed traits. Genotypes responded differently to salinity but all had a decreased tolerance index even at the lowest concentration of NaCl. The lowest percentages of dry leaves at 5 and 10 g NaCl·dm−3 were in K. glauca and S. caerulea. The percentage of dry matter and leaf greenness were least affected.